(2x-4)(3x-4)=

Simple and best practice solution for (2x-4)(3x-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-4)(3x-4)= equation:


Simplifying
(2x + -4)(3x + -4) = 0

Reorder the terms:
(-4 + 2x)(3x + -4) = 0

Reorder the terms:
(-4 + 2x)(-4 + 3x) = 0

Multiply (-4 + 2x) * (-4 + 3x)
(-4(-4 + 3x) + 2x * (-4 + 3x)) = 0
((-4 * -4 + 3x * -4) + 2x * (-4 + 3x)) = 0
((16 + -12x) + 2x * (-4 + 3x)) = 0
(16 + -12x + (-4 * 2x + 3x * 2x)) = 0
(16 + -12x + (-8x + 6x2)) = 0

Combine like terms: -12x + -8x = -20x
(16 + -20x + 6x2) = 0

Solving
16 + -20x + 6x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '2'.
2(8 + -10x + 3x2) = 0

Factor a trinomial.
2((4 + -3x)(2 + -1x)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(4 + -3x)' equal to zero and attempt to solve: Simplifying 4 + -3x = 0 Solving 4 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 0 + -4 -3x = 0 + -4 Combine like terms: 0 + -4 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333

Subproblem 2

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2

Solution

x = {1.333333333, 2}

See similar equations:

| 6+2(5x-4)=7-3(2x+1) | | 6x+4x-10=20 | | -16(x+5)+9x=-108 | | 8x^3+24x^2-32x=0 | | 4n-12-7n=6-2n | | 54-3x=-9 | | 24u^6w^4+10uw^2x^3= | | 11y+6+13y-6=360 | | -17y=136 | | 11y+6+13y-6=180 | | 7(1+6x)=175 | | 3(x^3)-12(x^2)+49(x)=504 | | 21x+6-x-5= | | 20u^3v^2x^7+15u^9v^5= | | 10=r+-6 | | x^3-4x^2+16x=168 | | -64=-8k | | 7(2n+3)=6(7n+7)+8 | | y=1.2*30-6 | | f(x)=2x^2+x^4+1 | | 41n(3x)=20 | | 5(x-6)=3(2x-2) | | 25v^2-120v=130v | | 22.5+2p=26.75 | | 27u^2x^6-9u^9x^5y^7= | | -6+4w=-26 | | (u+5)(u+5)=2u^2+u+43 | | 5x-1=4-3x | | -19=g-13 | | (v-7)(v-7)=2v^2-20v+54 | | 9(3n+2)=9(6n+6)+9 | | 6=3b |

Equations solver categories